2009
DOI: 10.1016/j.lungcan.2009.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in telomere maintenance genes, telomere length, and lung cancer susceptibility

Abstract: Telomeres are responsible for the protection of the chromosome ends and shortened telomere length has been associated with risk of multiple cancers. Genetic variation in telomere related genes may alter cancer risk associated with telomere length. Using lung cancer cases (n = 120) and population-based controls (n = 110) from Xuanwei, China, we analyzed telomere length separately and in conjunction with single nucleotide polymorphisms in the telomere maintenance genes POT1, TERT, and TERF2, which we have previo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
55
1
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(59 citation statements)
references
References 32 publications
2
55
1
1
Order By: Relevance
“…Jin Eun Choi et al found that 8 SNPs of hpot1 in which 2 SNPs are the risk factors in lung cancer (Choi et al, 2009). Hosgood, H. D also found hpot1 genetic variations in lung cancer tissues (Hosgood et al, 2009). Nan, H et al have demonstrated that there are hpot1genetic point variations in skin cancer (Nan et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…Jin Eun Choi et al found that 8 SNPs of hpot1 in which 2 SNPs are the risk factors in lung cancer (Choi et al, 2009). Hosgood, H. D also found hpot1 genetic variations in lung cancer tissues (Hosgood et al, 2009). Nan, H et al have demonstrated that there are hpot1genetic point variations in skin cancer (Nan et al, 2011).…”
Section: Discussionmentioning
confidence: 91%
“…First, hTERT has an important role at very early stages of carcinogenesis, its expression has been linked to increased susceptibility to tumorigenesis, and rs2075786 has been associated with cancer risk. 15,16,18,19,28,29 And second, through GWAS, genetic variants located in genes involved in telomere maintenance, and in particular in hTERT, were also associated with increased risk to cancer. [20][21][22][23][24][25][26][27] In contrast to previous studies examining the role of modifier genes, 11 our study includes two independent series of MMR gene mutation carriers, of 255 and 675 individuals, the latest being among the largest series used to study genetic modifiers of LS.…”
Section: Rs2075786 and Telomere Lengthmentioning
confidence: 99%
“…[20][21][22][23][24][25][26][27] Among the better characterized cancer variants, the hTERT rs2075786 (c.2654 þ 269G/A) SNP has been associated with lung cancer risk. 28,29 However, no studies have reported any association between variants located at the hTERT locus and the risk of CRC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several epidemiological studies (case-control and/or cohort) have reported on the association between TL and a number of cancers such as lung, 7,8 breast, [9][10][11] bladder, 12,13 renal, 14,15 gastric, 16,17 esophageal, 18,19 colorectal, 20,21 and lymphomas. 22,23 Interestingly, according to the most recent meta-analysis on TL and cancer, reported results of What's new?…”
mentioning
confidence: 99%